Synchronizing Metrics and Malasakit: A Hermeneutic Phenomenological Study of Transnational Filipino Special Education Teachers in the United States - Chavez, Rosemie; Archivido, Maria Luisa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the relationship between cultural identity and pedagogical practice through the lived experiences of Filipino Special Education (SPED) teachers in the United States. Anchored on Cultural Identity Theory, Sociocultural Theory, Pedagogical Content Knowledge, and Transactional Theory, the study examined how Filipino educators negotiated their cultural values, professional roles, instructional practices, and workplace interactions in multicultural U.S. school settings. A qualitative phenomenological research design was employed using Moustakas’s modified Van Kaam method. Six Filipino SPED teachers actively teaching in U.S. public or private schools participated in the study. Data were gathered virtually through semi-structured, in-depth interviews guided by a researcher-developed and expert-validated interview guide. The findings revealed five major themes: cultural identity and its influence on teaching, challenges in cultural adaptation and workplace communication, shifts in instructional practices to meet U.S. educational expectations, relationship-building with students and colleagues from diverse backgrounds, and professional and personal growth. Filipino values such as malasakit, bayanihan, pakikipagkapwa, compassion, patience, resilience, and respect shaped classroom management, instructional decisions, student engagement, and professional relationships. However, participants also experienced challenges related to communication differences, cultural adjustment, behavioral expectations, documentation requirements, and adaptation to student-centered, evidence-based, and data-informed instruction. The study concluded that Filipino SPED teachers developed hybrid pedagogical identities by blending Filipino relational values with U.S. special education practices, resulting in inclusive and supportive learning environments. The study recommends culturally responsive professional development, mentorship, intercultural communication support, collaborative professional communities, and institutional recognition of immigrant teachers’ cultural contributions. The study aligns with SDG 4, Quality Education, and SDG 10, Reduced Inequalities, by supporting inclusive education and recognizing the professional contributions of immigrant teachers. Its sustainability impact is primarily educational, institutional, and social, as it promotes culturally responsive teaching, teacher well-being, professional retention, and equitable learning environments.
Keywords: Bicultural Competence; Cultural Identity; Culturally Responsive Pedagogy; Filipino SPED Teachers; Hybrid Pedagogy; Immigrant Teachers; Pedagogical Practice; Professional Adaptation; Special Education; United States Education System